Bartonella Endocarditis and Pauci-Immune Glomerulonephritis: A Case Report and Review of the Literature. Issue 5 (September 2016) - Raybould, Jillian E.; Raybould, Alison L.; Morales, Megan K.; Zaheer, Misbah; Lipkowitz, Michael S.; Timpone, Joseph G.; Kumar, Princy N.
Abstract : Abstract: Among culture-negative endocarditis in the United States, Bartonella species are the most common cause, with Bartonella henselae and Bartonella quintana comprising the majority of cases. Kidney manifestations, particularly glomerulonephritis, are common sequelae of infectious endocarditis, with nearly half of all Bartonella patients demonstrating renal involvement. Although a pauci-immune pattern is a frequent finding in infectious endocarditis–associated glomerulonephritis, it is rarely reported in Bartonella endocarditis. Anti–neutrophil cytoplasmic antibody (ANCA) positivity can be seen with many pathogens causing endocarditis and has been previously reported with Bartonella species. In addition, ANCA-associated vasculitis can also present with renal and cardiac involvement, including noninfectious valvular vegetations and pauci-immune glomerulonephritis. Given the overlap in their clinical presentation, it is difficult to differentiate between Bartonella endocarditis and ANCA-associated vasculitis but imperative to do so to guide management decisions. We present a case of ANCA-positive Bartonella endocarditis with associated pauci-immune glomerulonephritis that was successfully treated with medical management alone.